Modelling Zika Virus, Dengue Fever and Chikungunya Virus: Gaining Insights into the Co-Dynamics of the Three Diseases (Journal of Nonlinear Modeling and Analysis, 2026)
The recent spike in the concurrent circulation of Zika, Dengue fever, and the Chikungunya virus poses a severe threat to public health, both at home and in the diaspora. This study dives into the interplay of these three diseases, applying mathematical analysis to explain their co-dynamics within a population where they coexist. A comprehensive investigation of the model indicates that the sub-models experience backward bifurcation when the relevant reproduction numbers for each disease fall below unity. To gain insights, real-life data from Espírito Santo State in Brazil, where both diseases are co-circulating and endemic, was gathered and incorporated into our model. This allowed us to estimate important parameter values that were embedded in the model. Through uncertainty and sensitivity analysis, we identified the top-ranked parameters that drive the spread of these three diseases, which are, effective contact rate of infected mosquitoes with susceptible humans, infected humans interacting with susceptible mosquitoes, and sexual transmission (specifically for the Zika virus). Simulations of the comprehensive Zika-Dengue-Chikungunya model revealed that minimizing the biting and contact rates of mosquitoes with humans decreases the disease load. Conversely, the absence of pesticide spraying and failure to utilize treated nets, together with unprotected sexual intercourse with sick individuals, result in the co-circulation of the three diseases, considerably aggravating the overall disease burden.
Keywords: Modeling; Zika virus; Dengue fever; Chikungunya; co-infection; stability analysis